PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN KECERDASAN SPIRITUAL TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Lipur Na'im; Kencana Dewi; Emylia Yuniartie (AKUNTABILITAS, 2013)
The purpose of this research is to determine the influence of modernizing tax administration system and spiritual quotient toward the level of individual taxpayers compliance in Kantor Pelayanan Pajak Palembang Ilir Barat either partially or simultaneously. The population of this reseach was 8.856 individual taxpayers who submit SPT 1770 to Kantor Pelayanan Pajak Palembang Ilir Barat. This reseach uses incidental sampling method and sample size used was 100 individual taxpayers who met by reseacher accidently. The data analysis technique in this reseach is multiple linier regression, F test, t test and coefficient of determination test (R2). The results of this research indicate that modernizing tax administration system and spiritual quotient simultaneously affect the level of individual taxpayers compliance. While the partial modernizing tax administration system affect significantly and positively the level of individual taxpayers compliance, and spiritual quotient do not affect significantly and positively the level of individual taxpayers compliance. Coefficient determination (R2) value in this research was 57.1%.